Niger : Leveraging Export Diversification to Foster Growth - World Bank (World Bank, Washington, DC, 2019)
Niger’s Vision 2035 acknowledges the country has little choice but to create ‘a competitive anddiversified economy.’ Economic diversification is a cornerstone component of the Economic Orientation Document (EOD) 2016-19 and the PDES 2017-21. The EOD defines Niger’s economic diversification as moving exports away from natural resources and increasing the value-added component of exports as the foundation for its agro-based industrialization and employment creation policies. Hence, an exports diversification strategy is akin to the country’s economic diversification and, not surprisingly, the PDES contains several axes of policy interventions supporting it. However, Niger faces serious structural challenges to diversify into new productive activities. The country is landlocked, exporting costs are high and, given multiple infrastructure and logistics gaps, access to markets is difficult beyond neighboring regional markets. Rapid population growth and low human capital turns into a low skilled population. Volatile economic growth, reliant on a few commodity exports that closely follow the vagaries of weather and boom and busts of international prices, makes hardly obtained poverty gains vulnerable.